Can the local government in Hungary be the appropriate local level framework for environmental sustainability? - Fodor, László (International Journal of Engineering and Management Sciences, 2019)
During the search for the framework for environmental (respectively social and economic) sustainability, the importance of local action / decision-making has been formulated several times. At the same time, the capability of local government structures is questioned from several aspects. Local governments today are not necessarily a proper legal-administrative framework for sustainable development, for example because the population of a sustainable local community (conceptually) and of a larger settlement (by size) does not coincide. However, the (partly networked) environmental policy system of the municipalities transcends the administrative area of the settlement, where appropriate, a larger area (agglomeration, city areas, etc.), connecting several actors and activities. The paper seeks to clarify this issue in two rather different but interrelating ways. The first approach is geographically rooted and examines the local government system and the spatial structure of the Hungarian state through environmental economics and environmental policy. The second question is about structural links, namely the problems of local governments potential for infrastructure development and the structure of the local economy. The paper concludes that municipal functions - administration, ownership, public service organization - are all concerned with environmental protection. Considering that many of the processes that are relevant to sustainability are taking place in settlements, so serious changes are needed at this level as well. In this context, cooperation between local and central government levels and the active involvement of (local) society can not be dispensed with, but the current mechanisms are hindering progress.